PENGARUH MOTIVASI, STRES KERJA, DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA NADARYA AVIATION CENTER MEDAN - Rachmawani; Indra Jaya; Elisabet Tambunan; Ivan Elisabet Purba; Santi Rizki (Smart Education, 2026)
This study aims to analyze the effect of Motivation, Job Stress, and Incentives on Employee Performance at Nadarya Aviation Center Medan. The aviation industry requires high professionalism, necessitating proper human resource management to maintain performance stability. The research method used is quantitative with an associative approach. The sample consisted of 115 respondents selected through total sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS 26. The partial test results (t-test) show that Motivation has a positive and significant effect on performance ( 5.294 > 1.981), Job Stress has a positive and significant effect on performance ( 5.428 > 1.981), and Incentives have a positive and significant effect on performance ( 7.454 > 1.981). Findings indicate that job stress in this environment acts as eustress that stimulates precision. Simultaneously (F-test), the three variables have a significant effect with 45.314 > 2.69 and a significance value of 0.000. The R-Square value of 0.667 indicates that Motivation, Job Stress, and Incentives contribute 66.7% to the variation in employee performance. In conclusion, the synergy between internal drive, pressure management, and financial reward schemes is the key to optimizing employee productivity at Nadarya Aviation Center